Local Anesthetic Systemic Toxicity in Total Joint Arthroplasty: Incidence and Risk Factors in the United States From the National Inpatient Sample 1998–2013. Issue 2 (1st February 2018) - Rubin, Daniel S.; Matsumoto, Monica M.; Weinberg, Guy; Roth, Steven
Abstract : Background: Local anesthetic systemic toxicity (LAST) is a rare and potentially devastating complication of regional anesthesia. Single-institution registries have reported a decreasing incidence, but these results have limited broad applicability. A recent study using a US database found a relatively high incidence of LAST. We used the National Inpatient Sample, a US database of inpatient admissions, to identify the national incidence and associated risk factors for LAST in total joint arthroplasties. Methods: In this retrospective study, we studied patients undergoing hip, knee, or shoulder arthroplasty, from 1998 to 2013, with an adjunct peripheral nerve blockade. We used a multivariable logistic regression to identify patient conditions, hospital level variables, and procedure sites associated with LAST. Results: A total of 710, 327 discharges met inclusion criteria. The average adjusted incidence was 1.04 per 1000 peripheral nerve blocks, with decreasing trend over the 15-year study period (odds ratio [OR], 0.90; P = 0.002). Shoulder arthroplasty (OR, 4.35; P = 0.0001) compared with knee or hip arthroplasty and medium-size (OR, 3.34; P = 0.003) and large-size (OR, 2.40; P = 0.025) hospitals as compared with small hospitals were associated with increased odds of LAST. Conclusions: The incidence of LAST nationally in total joint arthroplasty with adjunct nerve blocks is similar to recent estimates from academic centers, with a small decreasing trend through the study period. Despite an overall low incidence rate, practitioners should continue to maintain vigilance for manifestations of LAST, especially as the use of regional anesthesia continues to increase.